Morphological abnormality among regenerated shoots of banana and plantain (Musa spp.) after in vitro multiplication with TDZ and BAP from excised shoottips - Bidabadi, Siamak Shirani; Mahdavi, Fatemeh; Mahmood, Maziah (Academic Journals, 2009)
Five cultivars of Musa spp (banana and plantain); ‘Berangan Intan’, ‘Berangan’ (AAA), ‘Rastali’, ‘Nangka’ (AAB) and ‘Baka Baling’ (ABB) were chosen to compare the effect of benzylaminopurine (BAP) and thidiazuron (TDZ) on multiplication efficiency in relation with frequency of abnormal shoot regeneration. Shoot tips ofMusa spp. were cultured on MS medium supplemented with various concentrations (0.0, 11.1, 22.2, 33.3 and 44.4 µM) of BAP and (0.0, 0.5, 2, 5 and 7.5 µM) of TDZ. Increasing BAP above 22.2 µM and 33.3 µM increased the number of shoots in‘Berangan Intan’, ‘Berangan’, ‘Rastali’, ‘Nangka’ and ‘Baka Baling’ respectively, but above 33.3 µM significantly caused higher gross of abnormal shoot regeneration. TDZ in the media up to 2 µM for ‘Baka Baling’, ‘Nangka’ and ‘Rastali’ and 5 µM for ‘Berangan Intan’ and ‘Berangan’ increased the number of shoots per explant, however TDZ at 5 µM resulted in high number of abnormal shoots. In conclusion BAP at 22.2 µM and TDZ at 2 µM were assumed to be the most suitable for commercial micropropagation system with low frequency of abnormal shoot production for both banana and plantain.